Convergence on reduced stress behavior in the Mexican blind cavefish - Chin, Jacqueline S.R. (Dev Biol, 2018)
Responding appropriately to stress is essential for survival, yet in pathological states, these responses can develop into debilitating conditions such as post-traumatic stress disorder and generalized anxiety. While genetic models have provided insight into the neurochemical and neuroanatomical pathways that underlie stress, little is known about how evolutionary processes and naturally occurring variation contribute to the diverse responses to stressful stimuli observed in the animal kingdom. The Mexican cavefish is a powerful system to address how altered genetic and neuronal systems can give rise to altered behaviors. When introduced into a novel tank, surface fish and cavefish display a stereotypic stress response, characterized by reduced exploratory behavior and increased immobility, akin to “freezing”. The stress response in cave and surface forms is reduced by pharmacological treatment with the anxiolytic drug, buspirone, fortifying the notion that behavior in the assay represents a conserved stress state. We find that cave populations display reduced behavioral measures of stress compared to surface conspecifics, including increased time in the top half of the tank and fewer periods of immobility. Further, reduced stress responses are observed in multiple independently derived cavefish populations, suggesting convergence on loss of behavioral stress responses in the novel tank assay. These findings provide evidence of a naturally occurring species with two drastically different forms in which a shift in predator-rich ecology to one with few predators corresponds to a reduction in stress behavior.